By-catch associated with fisheries of Heterocarpus vicarius (Costa Rica) and Heterocarpus reedi (Chile) (Decapoda: Pandalidae): a six-year study (2004-2009) - Arana, Patricio M. (2013)
artículo (arbitrado) -- Universidad de Costa Rica. Centro de Investigaciones en Ciencias del Mar y Limnología (CIMAR), 2013